188k views
2 votes
Find the product. If the result is negative, enter "-". If the result is positive, enter "+".

-7(- a2 ) 2 ( -b3 )

Find the product. If the result is negative, enter "-". If the result is-example-1
User David Tew
by
5.1k points

2 Answers

5 votes

Answer:

7 a⁴ b³

Explanation:

-7 ( -a²)²( - b ³)

  • A negative base raised to an even power equals a positive

= -7 ( a²)² ( - b³)

  • Multiplying an even number of negative terms make the product positive

= - 7 ( a²)² × b³

  • simplify the expression by multiplying exponent

= (-7)( a²*² )× b³

= 7 a⁴ b³

User Ands
by
5.2k points
3 votes

Answer:

Solution given:

(-a²)=-a*-a=a²

-b³=-b*-b*-b=-b³

now

-7(-a²)²(-b³)=-7*a⁴*-b³=-7*-1 *a⁴b³=7a⁴b³

the product is 7ab³.

so

enter"+".

User Papakias
by
4.5k points